Assessment of the Live Attenuated and Wild-Type Edwardsiella ictaluri-Induced Immune Gene Expression and Langerhans-Like Cell Profiles in the Immune-Related Organs of Catfish - Kordon, Adef O.; Abdelhamed, Hossam; Ahmed, Hamada; Baumgartner, Wes; Karsi, Attila; Pinchuk, Lesya M. (Frontiers in Immunology, 2019)
Edwardsiella ictaluri is a Gram-negative intracellular pathogen that causes enteric septicemia of catfish (ESC). Successful vaccination against intracellular pathogens requires T cell priming by antigen presenting cells (APCs) that bridge innate and adaptive immunity. However, the evidence on immunological mechanisms that underscore E. ictaluri pathogenesis and the protective role of live attenuated vaccines (LAVs) is scarce. We assessed the expression of immune genes related to antigen presentation by real-time PCR and the distribution patterns of Langerhans-like (L/CD207+) cells by immunohistochemistry in the immune-related tissues of channel catfish challenged with two novel E. ictaluri LAVs, EiΔevpB, and ESC-NDKL1 and wild type (WT) strain. Our results indicated significantly elevated expression of IFN-γ gene in the anterior kidney (AK) and spleen of vaccinated catfish at the early stages of exposure, which correlated with increased numbers of L/CD207+ cells. In general, the ESC-NDKL1-induced IFN-γ gene expression patterns in the AK resembled that of the patterns induced by EiΔevpB. However the MHCII gene expression patterns differed between the strains with significant increases at 6 h post-challenge (pc) with the EiΔevpB and at 7 d pc with the ESC-NDKL1 strains, respectively. Significant increases in activity of T helper type polarization genes such as IFN-γ and T cell co-receptors after exposure to ESC-NDKL1, in combination with elevated numbers of L/CD207+ cells at 7 d pc with both LAVs compared to uninfected and the WT-exposed counterparts, were documented in the spleen. The dominant pro-inflammatory environment with dramatically overexpressed inflammatory genes in the AK and 7 d pc in the spleen in response to E. ictaluri was found in exposed catfish. In general, the pro-inflammatory gene expression profiles in the ESC-NDKL1 pc showed more similarities to the WT strain-induced gene profiles compared to the EiΔevpB counterpart. In addition, E. ictaluri WT significantly decreased the numbers of Langerhans-like L/CD207+ cells in the AK and spleen at 3 and 7 days pc. In conclusion, we report the differential framework of initiation of innate and adaptive immune responses between E. ictaluri strains with both LAVs having a potential of satisfying the stringent requirements for successful vaccines.